Estudio de la viabilidad técnico económica de un parque eólico offshore - Abril-Martorell García, Fernando (My University, 2014)
SUMMARY TECHNICAL AND ECONOMIC VIABILITY OF AN OFFSHORE WINDFARM Energy has always been a critical factor for the economic and social development of every country. That is the reason why energy has been the reason behind most of the world conflicts most in the last 70 years in the world. Its availability and price affect both developed and non-developed countries. Fossil fuel reserves are decreasing every year and the increasing difficulty to get them from a geographically point of view make renewable energy a good solution Available technology is developing steadily and reaching higher efficiency. However, big investments are required to obtain long term profits. In renewable energy, wind energy is the most developed technology taking advantage of higher efficiency and therefore better economics. There are two ways of producing energy with the wind: through land foundations (onshore) and sea foundations (offshore). The advantages of the offshore wind farms are shown below: - The wind resource presents excellent features on the sea due to stronger, constant and low roughness wind. - The technology avoids using land space. - Noise stops being a problem, and reduces the visual impact. - Owing to stronger winds, the wind turbines are bigger allowing them to generate more power. - Because of the complexity, of the technology it is labor intensive and therefore generates positive social and economic impact in the area. However, it also has disadvantages which are summarized below: - It requires big investments, and higher operational costs. - The construction is complex and needs experts and the latest technology. - There are limitations on the placement due to fishing areas or large maritime activities. Principal objective The main purpose of the project was to analyze the most important variables that affect directly to the economic viability of the wind farm. These variables were: the design of the cable connection between the wind turbines (risk of breaking), the total power of the wind farm (there are two different scenarios, 15 and 9 wind turbines) and the regulatory environment (3 cases regarding energy law).
Proyecto fin de carrera-Universidad Pontificia Comillas, Escuela Técnica Superior de Ingeniería (ICAI), Ingeniero Industrial. Director del proyecto: Francisco Fernández Daza.